Measuring the Determinants of Backward Linkages from FDI in Developing Economies : Is it a Matter of Size? - Sanchez-Martin, Miguel Eduardo (World Bank Group, Washington, DC, 2015)
The main focus of the paper is the measurement of the potential for externalities related to foreign direct investment. A series of novel proxies are drawn from the Enterprise Survey database of the World Bank-IFC and tested against hypotheses considered in the foreign direct investment literature. Using these proxies, an econometric assessment of the determinants of backward linkages in developing economies is presented. The results show that export-oriented foreign direct investment, wholly owned subsidiaries (as opposed to joint ventures), and foreign owned firms relying on foreign technologies are less likely to develop links with domestic companies. In addition, the analysis finds that some sectors (food, wood, auto, and auto-parts) are more prone than others (textiles and electronics) in developing backward linkages. Apart from the type of foreign direct investment and sector-specific characteristics, the size of the host economy matters. Foreign owned subsidiaries in most service oriented Caribbean islands buy a low percentage of inputs from domestic firms. This may be because in small islands there are not enough local suppliers with sufficient quality and capacity to meet the demands of multinationals. However, the paper presents the case of the Dominican Republic, the largest economy in the Caribbean, which has struggled to develop backward linkages because of the relative isolation of special economic zones from the rest of the economy.